PENGEMBANGAN MEDIA BIMBINGAN KLASIKAL BERBASIS APLIKASI LECTORA INSPIRE UNTUK MENGATASI PERILAKU BULLYING DI SMP 1 KALIWUNGU KUDUS - Agustini, Susi; Riyono, Ahdi; Gudnanto, Gudnanto (P2M STKIP Siliwangi, 2023)
The purpose of the research is to develop classical guidance media based on the Lectora Inspire application and determine the level of effectiveness of the media in overcoming bullying behavior in SMP 1 Kaliwungu Kudus. The research is Research and Development (R and D) using ADDIE model that consists of five stages: analyze, design, development, implementation, and evaluation. The instruments were observation sheets, interviews, questionnaires, validation sheets, and tests. The feasibility analysis shows that the validation of material obtained an average of 3.93 with a very good category, the validation of media obtained an average of 3.78 with a very good category, and the validation of the user obtained an average of 3.84 with a very good category. The analysis of increased knowledge about bullying of the students shows an average pretest score of 35.05 while the average posttest score of 61.08 with an increase of 74,27 % and the decrease in the level of bullying in students’ behavior from an average value of 95,85 to 56.67 with the decrease of 69,10 %. Based on the results of the T-test that determine the effectiveness of the media to increase the students' knowledge and the results of the Wilcoxon test that determine the effectiveness of classical guidance to change students’ behavior show that the development of classical guidance media based on the Lectora Inspire application is effective to overcome bullying behavior of the students in SMP 1 Kaliwungu Kudus.Keywords: Bullying, Classical guidance, Media, Lectora inspire